Enterohaemorrhagic Escherichia coli haemolysin is cleaved and inactivated by serine protease EspPα - Brockmeyer, Jens (Blackwell Publishing Ltd, 2011)
The haemolysin from enterohaemorrhagic Escherichia coli (EHEC-Hly) and the serine protease EspPα are putative virulence factors of EHEC. We investigated the interplay between these secreted factors and demonstrate that EspPα cleaves the 107 kDa large EHEC-Hly. Degradation was observed when purified EspPα was added to a growing culture of an EHEC-Hly-expressing strain, with isolated proteins and with coexpressing strains, and was independent of the EHEC serotype. EHEC-Hly breakdown occurred as a multistage process with the formation of characteristic fragments with relative molecular masses of ∼82 kDa and/or ∼84 kDa and ∼34 kDa. The initial cleavage occurred in the N-terminal hydrophobic domain of EHEC-Hly between Leu(235) and Ser(236) and abolished its haemolytic activity. In a cellular infection system, the cytolytic potential of EHEC-Hly-secreting recombinant strains was abolished when EspPα was coexpressed. EHEC in contact with human intestinal epithelial cells simultaneously upregulated their EHEC-Hly and EspP indicating that both molecules might interact under physiological conditions. We propose the concept of bacterial effector molecule interference (BEMI), reflecting the concerted interplay of virulence factors. Interference between effector molecules might be an additional way to regulate virulence functions and increases the complexity of monomolecular phenotypes.